Understanding development and proficiency in writing quantitative corpus linguistic approaches - Durrant, Philip 1976-; Brenchley, Mark 1981-; McCallum, Lee 1989- (Cambridge University Press, 2021)
"This is a book about how written language develops in English. In particular, it is about what one particular methodology - quantitative corpus linguistics (QCL) - can (and can't) tell us about such development. We conceptualize writing development as occurring along two main axes: time and quality. Development across time is exemplified by the texts reproduced in Figure 1.1. These were both written by school children in England: one by a 7-year old child in Year 2 of their education; the other by a 16-year old child in Year 11"--